A Magneto‐Reflectivity Study of CuInTe2 Single Crystals. Issue 1 (19th September 2019) - Yakushev, Michael V.; Faugeras, Clement; Mudryi, Alexander V.; Martin, Robert W.
Abstract : CuInTe2 single crystals are studied using optical magneto‐reflectance (MR) in magnetic fields B up to 20 T at 4.2 K. The spectra exhibit the A and B free excitons' blue shifting at increasing magnetic fields. Fitting quadratic functions to the experimental dependencies of the exciton spectral energy on B assuming a low field limit allow the determination of diamagnetic shift rates of 8.2 × 10 −5 and 8.5 × 10 −5 eV T −2 for the A and B free excitons, respectively. The excitons' reduced masses of 0.0575 m 0 and 0.0568 m 0 ( m 0 is the free electron mass), Rydbergs of 6.2 and 6.1 meV, and Bohr radii of 10.4 and 10.5 nm are then estimated. An electron effective mass of 0.062 m 0 and B sub‐band effective hole mass of 0.70 m 0 are determined using a literature value of the A valence sub‐band hole of 0.78 m 0 . Abstract : CuInTe2 single crystals are studied using optical magneto‐reflectance in fields up to 20 T. The A and B free excitons' reduced masses of 0.0575 m 0 and 0.0568 m 0 ( m 0 is the free electron mass) are determined assuming a low field limit. The electron and B exciton effective hole masses, Rydbergs, and Bohr radii are estimated using a literature value of the A exciton hole mass.